Pengaruh Model Pembelajaran Kooperatif Tipe Think Talk Write (TTW) Terhadap Keterampilan Berpikir Kritis - Jusmiati Jafar; Nur Zakiyah Randi; Henny Setiawati (Universitas Negeri Jakarta, 2026)
The 21st century is characterized by rapid change, innovation, and increasingly intense globalization. This condition demands individuals to have skills capable of facing various challenges. One of the skills that need to be possessed is critical thinking skills. Critical thinking skills are important for students to help in analyzing problems, evaluating, and identifying solutions to complex problems. The results of observations that have been carried out indicate that students' thinking skills are still not optimally developed. Steps that can be used are implementing cooperative learning Think Talk Write (TTW). The aim of this study was to determine the effect of the cooperative learning model Think Talk Write (TTW) on the critical thinking skills of class XI MIPA students at SMA Negeri 3 Enrekang. The design of this study was a one-group pretest-posttest design. The research instruments used were a critical thinking skills test and a student activity observation sheet. Data were analyzed using descriptive statistical analysis and inferential statistical analysis using the Paired Sample Test. The results showed that the average pre-test score of students' critical thinking skills was 35.25 in the